A MATURIDADE DO MODELO DE GESTÃO PARA REDUÇÃO DOS NÍVEIS DE PERDAS COMERCIAIS: O CASO DE UMA DISTRIBUIDORA DE ENERGIA ELÉTRICA - Costa, Artur Fernando de Souza (2005)
The purpose of this dissertation is to investigate the relations between the process of commercial and administrative losses and the management model and their implications in organization, for action within the context of changing from a sales center to a profit center and identify, based on sensitivity analyses of their main key value drivers, how changes in management practices can reduce the loss rate. The study is supplemented by an empirical section, in which several case studies involving ALFA Serviços de Eletricidade S.A. are reported and some of the concepts and approach methods are used in order to better adapt the processes and integrate the methodology applied, considering the formal aspects related to the specification of organizational and technical requirements. The main conclusions have been: (1) The study has identified the distributed energy, commercial losses, price of sale or rate, default and cost of energy, as the main business performance variable in the commercial area; (2) The evaluation of the key value drivers evidences that the results from commercial area must not be analyzed by global volume, but for the aggregate value per segment; (3) The study has evidenced that the residential segment is responsible for most of the positive revenues and operating margin, although it represents only 34% of the sales of energy in GWh with the higher cost of energy, while the industrial segment represents 28% of the energy invoiced with negative operating margin; (f) The fraud detection process is adversely affected by the deficiencies in the management system and by incomplete programs; (5) The study shows that commercial losses present a recursive behavior, in this case, the actions implemented to reduce the level of losses by theft of electric energy may rise the level of default, or vice-versa, ending up by being ineffective.